Effect of Psychobiotics on Psychometric Tests and Inflammatory Markers in Major Depressive Disorder: Meta-Analysis of Randomized Controlled Trials with Meta-Regression - Agata Misera; Paweł Liśkiewicz; Igor Łoniewski; Karolina Skonieczna-Żydecka; Jerzy Samochowiec (MDPI AG, 2021)
Probiotics were shown to act positively on gut-brain axis signaling. We aimed to assess the effect of the administration of a new class of probiotics-psychobiotics-using data from individual psychometric scales, markers of the immune system and neuroactive metabolites. Medical databases were searched from database inception until 22 April 2021 for randomized clinical trials in clinically proven Major Depressive Disorder (MDD) patients treated with either probiotics or placebo reporting any psychometric score (PROSPERO registration number: CRD42021253024). Ten studies with 705 randomized participants and 603 analyzed were included. The mean age of individuals was 38.43 ± 12.1 years, predominantly women (n = 461, 76.45). The mean study duration was 48.8 ± 12.3 (range = 28-62) days. The dosage ranged between 1 × 109 to 2 × 1010 colony forming units (CFU)/day. We found that probiotics might alleviate symptoms of MDD; endpoint data (pooled scores): SMD = −0.292, 95%CI = −0.577 to −0.007, p < 0.044; change scores (BDI): SMD = −0.482, 95%CI = −0.854 to -0.109, p < 0.011; DM = −4.848, 95%CI = −8.559 to −1.137, p < 0.01. The therapy tended to be more effective with time of psychobiotic supplementation (coefficient = −0.12, SE = 0.06, Z = −1.84, p = 0.06) and in men (% of females: coefficient = 0.1, SE = 0.06, Z = 1.78, p = 0.07). Psychobiotics have great potential in the treatment of MDD. However, no specific strain/strains, dosage or duration of treatment can currently be recommended.